High-Pressure Dielectric Studies-a Way to Experimentally Determine the Solubility of a Drug in the Polymer Matrix at Low Temperatures - Tajber, Lidia (My University, 2021)
In this work, we employed broad-band dielectric spectroscopy to determine the solubility limits of nimesulide in the Kollidon VA64 matrix at ambient and elevated pressure conditions. Our studies confirmed that the solubility of the drug in the polymer matrix decreases with increasing pressure, and molecular dynamics controls the process of recrystallization of the excess of amorphous nimesulide from the supersaturated drug–polymer solution. More precisely, recrystallization initiated at a certain structural relaxation time of the sample stops when a molecular mobility different from the initial one is reached, regardless of the temperature and pressure conditions. Finally, based on the presented results, one can conclude that by transposing vertically the results obtained at elevated pressures, one can obtain the solubility limit values corresponding to low temperatures. This approach was validated by the comparison of the experimentally determined points with the theoretically obtained values based on the Flory–Huggins theory.
PUBLISHED
Keywords: ASD; Dielectric spectroscopy; Solubility; High-pressure; Nimesulide; Kollidon VA64; Flory−Huggins theory; Nanoscience & Materials